The advancement of primary care dentistry in Hungary: progress of the dental cluster model since 2021 legislation - Sztrilich, András; Kaposvári, Csilla; Túri, Gergő; Teller, Rita; Vingender, István (Frontiers in Public Health, 2025)
BackgroundConsiderable changes in health policy in the area of publicly funded primary dental care in Hungary over the past 25 years have shaped primary care dentists’ financing, training and working conditions and the forms of association between dental providers. This study aims to describe the advancement of primary care dentistry in Hungary and the progress of the dental cluster model since the 2021 legislation.MethodsA mixed method study was designed that included a scoping review of the literature in December 2023 to collect information on the health policy developments of Hungary’s publicly funded primary dental care system; (b) secondary data analysis was carried out to assess the development of primary care dentistry and the formation and operation of dental cluster practices in Hungary.ResultsPrimary care dental clusters in Hungary were established to allow active professional cooperation within the dental clusters to improve the population’s access to preventive dental services and the quality of services. From its legislative base until December 31, 2023, 74 primary dental clusters were formed nationwide, representing 30% of dental practices. On average, the primary dental clusters contain nine practices. There is an uneven geographical distribution of primary dental clusters by counties. Up to the date of this research, primary care dental clusters were set up exclusively in the form of consortia. Adult and mixed dental practices, practices from county towns, county capitals and the capital city, as well as practices from districts with more dentists in the proportion of the population were more likely to join a dental group practice.ConclusionMonitoring and evaluating of the operation, performance and impact of primary care dental clusters in the future will provide important information about the Hungarian model.